Library
The Centre for Criminology and Sociolegal Studies Library houses the leading Canadian research collection of criminological material. Consisting of more than 25,000 books, journals, government reports, statistics and other documents, it is the largest resource of it’s kind in Canada. Through the Criminology Information Service (CIS), the Centre provides professional and innovative solutions to criminal justice communities worldwide. The information covers a wide range of subject areas, including public and private policing; violence; deviance and social control; young offenders; criminology, and criminal law